Panel Session-Pluriversal Design Transitions for Higher Education Motivated by COVID-19 - Guillen Mandujano, Lupita; Kuruc, Erdas; Lu, Jun-Li; Sanoni, Paola; Meza, Xanat Vargas (IEEE, 2021)
This panel provides an overview of how immersive learning technologies can be used for higher education in several non-Westernized contexts in the middle of the COVID-19 pandemic. Through the outline of pluriversal design combined with design transitions, we aim to explore how a world within which many worlds coexist can resurge from the present educational challenges and become a fairer, sustainable place for all.
7th International Conference of the Immersive-Learning-Research-Network (iLRN) -- MAY 17-JUN 10, 2021 -- ELECTR NETWORK
Keywords: design; transitions; higher education; COVID-19; immersive technologies